Effect of Application Nitrophenolates and IAA on growth and yield of Squash (Cucurbita pepo) - Zhala Neamat Sabr; Sawsan Mohammed Saeed (Zanco Journal of Pure and Applied Sciences, 2022)
A field experiment was conducted out from March 11th to July 20 th to study the effect of foliar application nitrophenolates (0, 2, 4 and 6 ml.l-1) biostimulators and IAA (0,150 and 300 mg. l-1) on the growth and yield of summer squash. Nitrophenolates had the best significant effect on plant length and shoot dry weight (63.12 cm and 98.72 g respectively) were obtained with 2 ml.l-1, leaf area (256.00 cm2) was measured in 4 ml.l-1 resentment. However, the best results of stem diameter (17.47 mm) was obtained from 300 ml.l-1 IAA. The interaction of 2 ml.l-1 nitrophenolates and 300 mg. l-1 IAA caused highest significant in Stem diameter (19.10 mm), plant length (69.20 cm) and fruit length (17.16cm), and the best results of fruit. weight Plot-1, fruit weight plant-1 and fruit weight hectare-1(7.30, 1.82 kg and 29.11 ton) were obtained from 150 ml.l-1 IAA without nitrophenolates treatments. 2 ml.l- nitrophenolates is the best levels significantly effect on vegetative and reproductive parameter, however the interaction between IAA and nitrophenolate more significantly effects.